Pengaruh Jenis Susu dan Persentase Starter yang Berbeda terhadap Kualitas Kefir - Yusdar Zakaria (Jurnal Agripet, 2009)
Effect of different milk and starter percentage on kefir qualityABSTRACT. The objective of this study is to study the quality of kefir with different amount of starter added and different kind of milk. The quality of kefir was evaluated by measuring lactic acid level, syneresis, crude protein, crude fat and amount of active microorganism. The result showed that the different percentage of starter and kind of milk has a high significant on syneresis and Lactic Acid level (P 0,01). The best interaction was resulted from the combination of 10% starter and UHT milk. The result also indicated that the different percentage of starter and kind of milk has no effect on crude protein, crude fat and the amount of active microorganism. The combination of 10% Starter and UHT milk, produces the best quality of kefir